Language Acquisition of Korean Children in an Indian Multilingual Society - Priya, Swati; Gouri, Sonia; Verma, Seema (Journal of Ecohumanism, 2025)
Indian society is linguistically diverse. There are multiple languages that are spoken in India. Small children have the capacity to learn language at a faster rate as compared to the adult. Language acquisition occurring in a particular context and differing environment are bound to influence the way language is learned and used by the young children. The children who are born and growing up in a linguistically diverse country like India are bound to have a different experience than those who encounter only one language. All these conditions will eventually have a profound impact on the social, linguistic and cognitive development of children. The present study has been focused on 12 Korean children who are growing up in Indian multilingual society. Through this paper an attempt has been made to highlight that how the children acquire language and what are the rate of the acquisition of phonetic sounds of the languages that they are exposed to.